2010
DOI: 10.1175/2010jcli3282.1
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Vertical Distribution across Warm and Cold Fronts in CloudSat–CALIPSO Data and a General Circulation Model

Abstract: Cloud vertical distributions across extratropical warm and cold fronts are obtained using two consecutive winters of CloudSat-Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) observations and National Centers for Environmental Prediction reanalysis atmospheric state parameters over the Northern and Southern Hemisphere oceans (308-708N/S) between November 2006 and September 2008. These distributions generally resemble those from the original model introduced by the Bergen School in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 45 publications
4
80
0
Order By: Relevance
“…It is clear that the cloud fraction in ISCCP is far greater than for HiGEM and ERAI, indicating that ISCCP observes more cloud around ETCs than in either HiGEM or ERAI. Other studies (see Zhang et al 2005;Kay et al 2012, and references therein) have shown that climate models typically underestimate total cloud amounts globally and this has been shown to extend to biases around ETCs and fronts (e.g., Naud et al 2010Naud et al , 2014. All three datasets have peak cloud fractions in a region which is centred on the peak precipitation and maximum ascent (as shown in Fig.…”
Section: Isccp Composite Storm Structurementioning
confidence: 77%
See 1 more Smart Citation
“…It is clear that the cloud fraction in ISCCP is far greater than for HiGEM and ERAI, indicating that ISCCP observes more cloud around ETCs than in either HiGEM or ERAI. Other studies (see Zhang et al 2005;Kay et al 2012, and references therein) have shown that climate models typically underestimate total cloud amounts globally and this has been shown to extend to biases around ETCs and fronts (e.g., Naud et al 2010Naud et al , 2014. All three datasets have peak cloud fractions in a region which is centred on the peak precipitation and maximum ascent (as shown in Fig.…”
Section: Isccp Composite Storm Structurementioning
confidence: 77%
“…The CloudSat (known as Quickbeam) simulator (Haynes et al 2007;Bodas-Salcedo et al 2011) provides the ability to directly compare equivalent fields from CloudSat and reanalysis/forecast/climate models (e.g., Bodas-Salcedo et al 2008;Greenwald et al 2010;Naud et al 2010;Govekar et al 2011;Field et al 2011;Jiang et al 2012;Franklin et al 2013;Govekar et al 2014;Booth et al 2013). The simulator works by distributing model hydrometeors amongst the sub-grid columns with radar reflectivity, including attenuation, calculated at each model level.…”
Section: Cospmentioning
confidence: 99%
“…In global scale models (e.g., general circulation model (GCM)) and regional models with coarse grid spacing, shallow clouds are usually expressed by parameterizations (e.g., Tiedtke 1993;Considine et al 1997;Kain 2004), but these parameterizations have not been able to effectively simulate the shallow cloud cover observed from satellites (e.g., Chepfer et al 2008;Naud et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Shallow clouds have been expressed by parameterizations in global-scale models (e.g., Tiedtke 1993;Considine et al 1997). However, the parameterizations have not been able to simulate the shallow cloud cover observed from satellite (e.g., Chepfer et al 2008;Naud et al 2010); thus, it is necessary to improve understanding of the characteristics and parameterizations of shallow clouds to reduce uncertainties in climate prediction.…”
Section: Introductionmentioning
confidence: 99%